REPRESENTASI PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA LITERASI TENTANG ANTISIPASI CYBERCRIME (STUDI DESKRIPTIF PADA AKUN MALAMTANPAKATA) - Fauziah Fauziah (Prodi Ilmu Komunikasi Universitas Putera Batam, 2026)
Social media Twitter is a social media that is currently popular again after it was previously popular in 2011. With the presence of Twitter, an issue can become a viral phenomenon when it gets a lot of attention from Twitter social media users. Through a thread on Twitter, the user could tell the story of the event and the chronology in detail. One of them is the chronology of crimes that happen in the virtual world, namely lovescam which is currently called tinder swindler inspired by the Netflix series called